SUBSTITUSI BEKATUL PADA PEMBUATAN BISKUIT TERHADAP PENINGKATAN KADAR SERAT SEBAGAI JAJANAN TINGGI SERAT - Hendrayati Hendrayati (Media Gizi Pangan, 2019)
ABSTRACT Obesity in Indonesia is still a serious health problem. The accelerating progress of The Times has resulted in unhealthy diet changes. One of the most common habits of ingesting high fat but low fiber. The bran is one of the high-fiber food items that can be used as a high fiber alternative food. One of a food products that can be served as food or a high fiber snack that is a biscuit in substitution. The study was intended to determine the effect of the substitution of the paste in the making of biscuits in the increase in fiber levels as high fiber snacks. Research design is an experiment with the posstest only design group. The fiber analysis uses the crude fiber method to measure the fiber level of the biscuit with a concentration of 0%, 10%, 20%, and 30%. Studies indicate that the higher the concentration of these added amounts to the higher the concentration of the fibers. Crackers with the highest fiber substitution 30% concentrations with a rate of 28.37%. Bran biscuits could be recommended for snacks or high fiber snacks. It is recommended to develop food products with beshed food and analyze other nutrients.